Effect of Diets Containing Different Qualities of Barley on Growth Performance and Serum Amylase and Intestinal Villus Morphology - Moharrery, A.; Mohammadpour, A.A. (International Journal of Poultry Science, 2005)
A study was conducted to investigate protein metabolism and differences in length of intestinal villi in broiler chickens which consumed one of the barley based diets. The treatments were corn diet (1) as a control, barley diet with (4) or without (2) a commercial β-glucanase enzyme, barley treated with rumen fluid without protozoa (3) and hulless barley (5). The effect of treatments were investigated in a 42 d trial using 360 sexed, broiler chickens. In a digestibility trial, 15 male broiler chicks were used at 45 days old. In this regard, five treatments offered to chicken in three replicates individually. The experimental design for performance investigation was a completely randomized one with a 5 x 2 factorial arrangement of treatments. Each of five treatments was replicated three times per sex (n = 3). The levels of barley in treatments of (2) to (5) were 35% during growing (14 to 42 d) and finishing (42 to 52 d) periods. At the end of trial, two birds from each pen were selected and slaughtered. For histological studies the length, width and surface area of intestinal villi has been determined on male chickens. Blood sample has been taken just before slaughter of birds. No significant difference (P>0.05) was observed between (3) to (5) treatments with corn diet for weight gain, feed intake and feed conversion, but barley with no treatment (2) has shown less weight gain to compare enzyme treatment and hulless barley diet (P< 0.05). Digestibility of dry matter (DM) and crude protein (CP) were less in barley diet with no treatment, to compare other treatments (P< 0.05).